The concept and content of the contract of participation in shared construction and its legal characteristics - A. E. Kolieva; G. G. Khachiev; F. G. Konova (Правоприменение, 2022)
The subject of the research is the contract of participation in shared construction. This type of contract is characterized by a special subject structure and defined as independent bilateral commercial agreement owing to which it stands out of other types of contracts. The practice of using this legal institution shows its possibilities and advantages in terms of increasing the number of citizens who have received the opportunity to improve their housing conditions. Nevertheless, today in Russia there is a question of stopping the use of shared-equity construction because there are also negative aspects of the implementation of this right, including an increase in the number of defrauded shareholders. The ambiguity of this legal institution throughout the history of its existence has been the subject of study by many scientists. One of the main issues of these studies was the equity participation agreement as a form of expression of legal relations between developers and participants in shared construction, which provides protection of the rights of all parties to the specified transaction. The equity participation agreement is the basis of legal relations between the parties and regulates their rights and obligations.The purpose of this article is to investigate the main features of the contract in shared construction, to summarise different points of view on the definition of this legal document, to consider the algorithm of concluding this kind of contract, to review Russian legislation in the sphere of shared construction, Russian judicial practice and negative aspects of buying real estate units under this type of contracts.Methodology. A systematic approach was used in combination with logical methods of cognition. It made it possible to study the theoretical, factual and legal grounds of the phenomenon of shared construction in Russia.The main results, scope of application. The article stipulates the main features of the contract of shared construction, different points of view on the definition of this kind of contracts, the algorithm of concluding a contract of shared construction and Russian judicial practice in this sphere.